Role Models and Life Histories of Teacher Trainers as Tools for Effective Teacher Education: A Case for Geography Teacher Trainers in Uganda - Kagoda, Alice Merab (Richtmann Publishing, 2011)
Two hundred (310) undergraduate and postgraduate students participated in this study. The participants wererequested to write down the best and worst teachers in their life right from primary to high school which is 14 years of schooling.They had to identify qualities that made that teacher good/and role model and likely to influence their development as geographyteachers. Results show that students value and love teachers that are intelligent and have good knowledge of the subject matter,approachable, morally upright, approachable/accessible, honest and guides the students, smartly dressed and presentable.They particularly liked geography teachers that used the environment round the school as a laboratory making the subject realand relevant, used fieldwork as a method of teaching, use of maps, pictures, graphs regularly in class. They particularly hatedteachers who sexually abused students, discriminated against dull students, had no teaching aids, didn’t mark books,consequently no feedback, no fieldwork in Geography. Through discussions and peer teaching teacher trainees demonstratedtheir creativity through the teaching methods and materials they used. They promised to continue developing alternativeteaching methods and materials for their own professional career development